Meningkatkan posisi tawar petani di perbatasan Indonesia - Malaysia - Agil Judistira; Ferdy Zuniansyah; Bayu Dalang Pamungkas; Nungki Kusumatuti; Fransiska Kurniati; Fariastuti Djafar; Supriaman Supriaman (Penamas: Journal of Community Service, 2026)
Pisak Village, as one of the villages on the Indonesia-Malaysia border, has great potential as a vegetable producer for domestic and cross-border markets. Vegetable farmers in Pisak Village face real problems in the form of high dependence on middlemen in marketing their crops, resulting in a weak position for farmers and unprofitable selling prices. Furthermore, uncontrolled price pressures, limited access to cross-border markets in Malaysia, a lack of farmer economic institutions, and poor post-harvest infrastructure make it difficult for farmers to maintain stable, sustainable incomes. This Community Service (PkM) activity aims to improve farmers' bargaining position by conducting outreach training on product processing and courage-based promotion. Through product processing, farmers are expected to increase the added value of their agricultural products, while courageous promotion is expected to open wider market access. Implemented through an interactive socialization and discussion approach, this PkM activity not only focuses on improving farmers' technical skills but also on strengthening market access and economic institutions, thereby creating independence and economic sustainability for the Pisak Village community in the border region.